DIVERSITAS GENDER, ESG, DAN KINERJA PERUSAHAAN - Ranty Anindyastri; Tastaftiyan Risfandy (MANAJEMEN DEWANTARA, 2025)
Purpose: This study investigates the influence of board gender diversity on firm performance, mediated by ESG performance. It focuses on manufacturing firms in Indonesia, where sustainable practices and inclusive governance are increasingly relevant. Methodology: Using panel data from 27 manufacturing firms that listed on the Indonesia Stock Exchange during 2015–2023 (243 firm-year observations), this study measures gender diversity by the percentage of female board members, ESG performance by ESG scores, and firm performance by Return on Assets (ROA). Panel regression analysis is conducted with EViews 13, including a Sobel test to examine mediation effects. Findings: The results reveal that gender diversity positively affects ESG performance. Both gender diversity and ESG performance significantly enhance firm performance. Moreover, ESG performance partially mediates the relationship between gender diversity and firm performance. These findings highlight the strategic value of gender-inclusive boards in driving sustainability and profitability.